Assessment of level of knowledge, attitude, and associated factors toward delirium among health professionals working in intensive care unit multicenter, cross-sectional study, Amhara region comprehensive specialized hospitals, Northwest Ethiopia, 2023 - Ayanaw Eyayu, Ruth; Gudayu Zeleke, Tadael; Chekol, Wubie Birlie; Yaregal Melesse, Debas; Enyew Ashagrie, Henos (Frontiers in Public Health, 2024)
Background: Patients in Intensive Care Unit (ICU) are at high risk of developing delirium. Challenges are facing in early detection and management of delirium in ICU.This study aimed to assess the level of knowledge, attitude and associated factors towards delirium among healthcare providers working in ICU.A multicenter, cross-sectional survey was conducted in Comprehensive Specialized Hospitals from April 15-June 5, 2023. Data were collected using pretested self-administered questionnaire. Ordinal logistic regression analysis was performed at P < 0.05 with 95% confidence interval (CI). The odds ratio with 95%CI was calculated to determine the strength of association between independent and outcome variables.Results: A total of 202 health professionals were included in this study with a response rate of 87%. The proportions of good, moderate and poor knowledge towards delirium in ICU were 29.21 (95% CI: 23-36), 52.48 (95% CI:45.3-59.5) and 18.32 (95% CI:13.2-24.4) respectively. The overall proportion of negative, neutral and positive attitude were 13.9 (95% CI: 9.4 -19.4), 65.8 (95% CI: 58.9 -72.4) and 20.3 (95% CI:15-26.5) respectively. Being an anesthetist and exposure to training were positively associated with good knowledge, while, belief on screening tool to change care and reading and use of guidelines were positively associated with positive attitude. However, believing the impossibility of changing the practice of delirium care and negative attitudes were delaying factors for good knowledge. Also, workload and poor knowledge were hindering factors for positive attitude.More than half of health professionals had moderate knowledge and neutral attitude towards delirium. However, some proportions of them were with poor knowledge and negative attitude. We recommend stakeholders prepare regular training for delirium care. Also, we urge health professionals to update themselves by reading guidelines and to use screening protocols for delirium.